Modification of the existing maximum residue levels for fosetyl/phosphonic acid in citrus fruits resulting from the use of potassium phosphonates - EFSA (European Food Safety Authority) (Wiley, 2021)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Luxembourg Industries (Pamol) Ltd submitted a request to the competent national authority in Spain to modify the existing maximum residue levels (MRLs) for fosetyl/phosphonic acid (fosetyl‐Al (sum of fosetyl, phosphonic acid and their salts, expressed as fosetyl)) in citrus fruits. Adequate analytical methods for enforcement are available to control the residues of potassium phosphonates according to the existing and proposed residue definitions for enforcement in the commodities under consideration. Since EFSA raised concerns regarding the independence of some of the residue trials submitted in support of the MRL application, EFSA presented three options of MRL proposals for further risk management consideration. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of potassium phosphonates on citrus crops according to the reported agricultural practices is unlikely to present a risk to consumer health.